Hierarchical Structures from Inorganic Nanocrystal Self-Assembly for Photoenergy Utilization - Yun-Pei Zhu; Tie-Zhen Ren; Tian-Yi Ma; Zhong-Yong Yuan (International Journal of Photoenergy)
Self-assembly has emerged as a powerful strategy for controlling the structure and physicochemical properties of ensembles of inorganic nanocrystals. Hierarchical structures from nanocrystal assembly show collective properties that differ from individual nanocrystals and bulk samples. Incorporation of structural hierarchy into nanostructures is of great importance as a result of enhancing mass transportation, reducing resistance to diffusion, and high surface areas for adsorption and reaction, and thus much effort has been devoted to the exploration of various novel organizing schemes through which inorganic porous structure with architectural design can be created. In this paper, the recent research progress in this field is reviewed. The general strategies for the synthesis of hierarchical structures assembled from nanobuilding blocks are elaborated. The well-defined hierarchical structures provide new opportunities for optimizing, tuning, and/or enhancing the properties and performance of these materials and have found applications in photoenergy utilization including photodegradation, photocatalytic H2 production, photocatalytic CO2 conversion, and sensitized solar cells, and these are discussed illustratively.